The Impact of Different Factors on Repeat Visits to Selected International Tourism Enterprises: Case Study From Czechia - Kajzar, Patrik (Frontiers in Psychology, 2022)
The aim of this article is to identify the influence of the different factors on the repeat visits to selected international tourism enterprises based on the responses of customers in Czechia. The selected factors were divided into three main groups: service, environment, and offer, and each of these groups consists of other different factors. Primary data were analyzed using SPSS software. Statistical hypotheses were formed, reflecting the relationship between the difference in customer responses and selected quality factors, which can affect repeated visits to selected tourism enterprises. Most customers of repeat visits to selected tourism enterprises are affected by professional behavior, staff empathetic approach, offer knowledge and ability to provide as much information as possible, cleanliness and tidiness, overall atmosphere of the establishment, lighting and thermal comfort, air cleanliness, and plenty of space, taste and quality of food and ingredients, and last but not least also corresponding ratio of price/quality, good experience and attractive price level. Studying consumer behavior is important because it helps marketers understand what influences consumers' buying decisions not only in the tourism area in the Czechia but can fill in the market gap and identify the new products and services that are needed.